2020
DOI: 10.3390/mi11020127
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Platform for Individual Coral Polyps Culture and Monitoring

Abstract: Methodologies for coral polyps culture and real-time monitoring are important in investigating the effects of the global environmental changes on coral reefs and marine biology. However, the traditional cultivation method is limited in its ability to provide a rapid and dynamic microenvironment to effectively exchange the chemical substances and simulate the natural environment change. Here, an integrated microdevice with continuous perfusion and temperature-control in the microenvironment was fabricated for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Although in the present study, experiments were conducted only until 5 days postbail-out, recovered polyps survived for over 2 weeks in our preliminary experiments, without strict monitoring of recovery conditions (data not shown). This lifespan is comparable to those reported in previous studies applying microfluidic techniques for post-bail-out polyp cultivation, in which recommencement of skeletogenesis was even observed (Shapiro et al, 2016;Luo et al, 2020;Pang et al, 2020). Based on morphological observations and computational modeling, Pang et al (2020) suggested that continuous supply of DO (dissolved oxygen) and DIC (dissolved inorganic carbon) is essential for long-term cultivation of isolated polyps.…”
Section: Recovery Of Coral Polyps After Bail-outsupporting
confidence: 85%
See 1 more Smart Citation
“…Although in the present study, experiments were conducted only until 5 days postbail-out, recovered polyps survived for over 2 weeks in our preliminary experiments, without strict monitoring of recovery conditions (data not shown). This lifespan is comparable to those reported in previous studies applying microfluidic techniques for post-bail-out polyp cultivation, in which recommencement of skeletogenesis was even observed (Shapiro et al, 2016;Luo et al, 2020;Pang et al, 2020). Based on morphological observations and computational modeling, Pang et al (2020) suggested that continuous supply of DO (dissolved oxygen) and DIC (dissolved inorganic carbon) is essential for long-term cultivation of isolated polyps.…”
Section: Recovery Of Coral Polyps After Bail-outsupporting
confidence: 85%
“…In recent decades, advances in microfluidic and molecular techniques have made it possible for coral research at polyp scale, the basic building blocks of coral colonies (Bromage et al, 2009;Shapiro et al, 2016;Luo et al, 2020;Pang et al, 2020). Individual polyps enable detailed visualization of cellular and molecular responses in corals, which is typically constrained at colony scale by the calcareous skeletons.…”
Section: Introductionmentioning
confidence: 99%
“…Osmoregulatory stress (increase in salinity of >15‰) has been shown to induce polyp bailout in three different pocilloporid coral genera (Chuang et al, 2021;Chuang & Mitarai, 2020;Liu et al, 2020;Shapiro et al, 2016). Two other recent studies used calcium-free seawater as an artificial stressor to induce bailout in pocilloporid corals (Luo et al, 2020;Pang et al, 2020).…”
Section: Stressors Known To Induce Polyp Bailoutmentioning
confidence: 99%
“…Luo et al studied the numerical simulation of oxygen and glucose transport to improve the functionality of biomedical microfluidic devices. They designed an integrated microfluidic device for the culture of individual coral polyps, including a uniform flow medium, rapid mass transfer, and precise temperature control [9]. The microfluidic device provided a reliable analytical approach for model and mechanism studies of coral bleaching and reef conservation.…”
Section: Cell Tissue and Organ Culture Platformsmentioning
confidence: 99%